Study of output difference of two different ionization chambers for large fields used in radiotherapy - A. Hegazy, Ehab (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Many radiotherapy centers don’t pay attention to effect of ionization champers type on accuracy of quality control measurements. They use any available ionization champers in all quality control and data entry measurements (1,2) . Many studies were carried out in this field to compare different ionization champers in small fields but large fields were not completely compared before (3.4). The aim of this work is to compare output factor in large field using two different sizes ionization champers connected to electrometer. Final out put were obtained from the farmer and smidflex dosimeter irradiated with 6 MV photon beams. Important field side ranging from 20 cm to 70 cm side field is measured in whole body radiation (5, 6). For all examined large field sizes a difference ranging from 1% to 5 % was found when added to other calibration errors it will exceeds the acceptable margin. The largest difference was found in field side 70 cm this may be due to large scattering radiation